Trends of number of patient visits, demographic, and patient diagnosis at a dental hospital during the COVID-19 pandemic: a descriptive study - Siboro, Sarah Velita; Suryanti, Netty; Putri, Fidya Meditia (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: The long-standing COVID-19 pandemic had resulted in the implementation of service restrictions and the emergence of patients' fear of coming to health facilities, which could have caused changes in patient visit trends. The aim was to determine trends in the number of visits, demographic characteristics and patient diagnoses during the COVID-19 pandemic. Method: the descriptive and population research used secondary data from medical records of new visiting patients and existing patients at the general dental clinic, pavilion clinic, and emergency ward at the Universitas Padjadjaran Dental Hospital (RSGM UNPAD) from April 2019 to March 2021. Sample for number of patient visits before and during the pandemic, the total sampling was 12,714 and the characteristics and diagnosis of patients during the pandemic were 3,625 medical records, while non-probability sampling technique with purposive sampling was used. Univariate analysis used frequency distribution, line charts, bar charts. Result: The number of patient visits at RSGM UNPAD during the pandemic decreased by around 60% (from 9,089 to 3,625 visits) compared to before the pandemic. The patient demographics during the pandemic at RSGM and at its three polyclinics were relatively the same: adults (26-45 years), female, domiciled in the city of Bandung, private employees, Moslem, Sundanese, unmarried, and past patient status.The most common diagnosis at RSGM was pulpitis 914 (61%); in general dental polyclinic was pulpitis 751 (33%); in the pavilion clinic was malocclusion 428 (32%) and in the emergency ward was pulpitis, necrosis of pulp and impacted each 4 (16%). Conclusion: During the COVID-19 pandemic, patient visits to the dental hospital decreased more than half, the demographic characteristics of the three polyclinics were relatively the same and the most common patient diagnosis was pulpitis.KEYWORDS : Demographics; dental hospital; oral diagnosis; the COVID-19 pandemic; trend of patient visits